Papillary Fibroelastoma: A Rare Cardiac Tumor - Brazill, Perri (Operating Room Nurses Association of Canada Journal, 2001)
Cardiac papillary fibroelastoma is a rare, benign, primary tumor of the heart and accounts for seventy—eight percent of cardiac tumors. Patient are usually asymptomatic although there is a signiﬁcant risk for embolization. Papillary fibroelastomas usually arise from the cardiac valves. This is a case presentation of a patient who was admitted to our institution and his course of treatment leading to excision of the cardiac papillary fibroelastoma.